Projection-Type Multiview Holographic Three-Dimensional Display Using a Single Spatial Light Modulator and a Directional Diffractive Device - Yanfeng Su; Zhijian Cai; Kai Wu; Lingyan Shi; Feng Zhou; Haidong Chen; Jianhong Wu (IEEE Photonics Journal)
In this paper, we propose a projection-type multiview holographic three-dimensional (3-D) display using a single spatial light modulator (SLM) and a directional diffractive device, where a phase-only Fresnel hologram is calculated and displayed on the SLM to reconstruct the multiview hybrid image of a 3-D object for providing the amplitude information of a multiview light field, and a directional diffractive device covered with many pixelated gratings is designed to guide different reconstructed perspectives into different viewing zones for expressing the phase information of the light field. Furthermore, a four-view directional diffractive device is fabricated by using the pixelated holographic exposure method, and its optical properties are also measured under a collimated illumination of the green reconstruction laser with the designed wavelength. In addition, an experimental verification system is constructed to demonstrate a four-view 3-D display. The recorded experimental results confirm that a crosstalk-free four-view light field is created, which is beneficial from the precise alignment between the directional diffractive device and the reconstructed image. Moreover, the capability of dynamic display with the proposed system is also tested by refreshing the SLM with the sequential holograms, and the captured videos show a promising potential for the real-time multiview holographic 3-D projectors.